Application and research progress of phase change materials in biomedical field. (5th August 2021) - Ma, Kunlin; Zhang, Xuelai; Ji, Jun; Han, Lu; Ding, Xingjiang; Xie, Wenhao
Abstract : Application of phase change materials (PCMs) in biomedical field. Abstract : Phase change materials (PCMs) are widely used in solar energy utilization, industrial waste heat recovery and building temperature regulation. However, there have been few studies on the application of PCMs in the field of biomedicine. In recent years, some scholars have carried out research in the biomedicine field using the characteristics of PCMs. It was observed that the excellent properties of PCMs enhance the quality of a variety of biomedical applications with many advantages over existing applications, which provide new methods for the treatment of disease. PCMs have broad application prospects in the field of biomedicine. Therefore, a timely review of relevant research progress is of great significance for the continuous development of new methods. Innovatively, from the unique perspective of the biomedical field, this paper systematically reviews the application and related research progress of PCMs from four aspects: cold chains for vaccines and medicines, drug delivery systems, thermotherapy/cold compress therapy and medical dressings. In addition, we summarize and discuss the general principles of the design and construction of PCMs in the biomedical field. Finally, existing problems, solutions and future research directions are also put forward in order to provide a basis for guidance and promote the future applications of phase change materials in the biomedicine field.